(untitled) (Itinerarios Educativos, 2020)
In a context of poverty but with a high schooling rate, this work is intended to elucidate if children in Córdoba, Argentina, show differences in their academic achievement (AA) trajectories associated with socioeconomic characteristics. A prospective cohort study was conducted with schoolchildren, in which annual measurements of AA and baseline measurements of social characteristics were collected: sex, mother’s educational level, parental occupational stratum, socioeconomic level (SEL) and intellectual capacity (IC). Four categories were defined for academic achievement trajectories according to their scores obtained in the subjects of Language and Mathematics at the beginning and end of the conducted analysis, and in relation to their promotion or not to the next grade by the end of each school year. The four categories for trajectories were: distinguished, satisfactory, regular, and unsatisfactory. Binomial and multinomial logistic regression models were used to examine the presence of social inequalities. Significant differences were found in academic achievement trajectories depending on the studied socioeconomic variables, whose effects were not independent of the intellectual capacity. Intellectual capacity was strongly associated with mother’s educational level, parental occupational stratum, and SEL. The influence of social inequalities on intellectual capacity and academic achievement trajectory was proved.